Analysis of Product Quality, Promotion, and Price Factors in Forming Consumer Purchasing Decisions - Djupiansyah Ganie; Siti Munawaroh; Sayugo Adi Purwanto; Rapika Puspita Sari (Pusat P2M Politeknik Negeri Batam, 2025)
Product quality is crucial in retaining customers, so it is often interpreted as anything that satisfies consumers or meets their requirements and needs. The purpose of this study is to determine the effect of product quality, promotion, and price on consumer purchasing decisions at the Dian Shop in Tanjung Redeb. The number of population visits in this study is estimated from the average number of customer visits per day, which is 90 people, resulting in approximately 2,700 customers per month. The respondent sampling technique was employed using the accidental sampling method, which is based on chance. The number of samples was determined using the Slovin formula, based on the assumption of an average of 90 customer visits per day. The study sample consisted of 96 consumers who shopped at the Dian Shop. This research method uses multiple linear regression analysis, and the data analysis tool used is SPSS 26. The findings indicate that product quality, promotion, and price have a significant influence on consumer purchasing decisions, both simultaneously and partially. Thus, the research hypothesis is accepted. These findings underscore the importance of these three elements in shaping consumer purchasing behavior within a retail environment.